Paleomagnetic study on the Triassic rocks from the Lhasa Terrane, Tibet, and its paleogeographic implications. (1st May 2016) - Zhou, Yanan; Cheng, Xin; Yu, Lei; Yang, Xingfeng; Su, Hailun; Peng, Ximing; Xue, Yongkang; Li, Yangyang; Ye, Yakun; Zhang, Jin; Li, Yuyu; Wu, Hanning
Highlights: We carried out paleomagnetic study on the new discovered and redefined Triassic strata. Two reliable poles from Triassic strata of Lhasa Terrane were obtained. At those successful constrains, the tectonic evolution of the Lhasa Terrane of the Tibetan Plateau were reconstruct. Abstract: We present paleomagnetic results from the newly discovered Early-Middle and Late Triassic marine sediments of the Lhasa Terrane. Orientated samples were collected from 32 sites (330 samples) on the north side of the Dibu Co Lake (84.7°E, 30.9°N), Coqên County, in the western region of the Lhasa terrane. Rock magnetic data revealed that most of the samples were dominated by magnetite and/or pyrrhotite. The stepwise demagnetization curves illustrated three-components: a low temperature component (Component A) near the present-day field (PDF), a secondary remanent magnetization (Component B) that may be from the Cretaceous Period, and a high-temperature component (Component C). The Component C were isolated from the Early-Middle Triassic rocks in 8 sites (47 specimens) and from the Late Triassic rocks in 6 sites (37 specimens). The Component C of the Early-Middle Triassic rocks passed a reversal test (B class, 95% confidence level) and a fold test (99% confidence level), that of the Late Triassic rocks passed a fold test (95% confidence level). The corresponding paleopoles for the Early-Middle and Late Triassic periods of the Lhasa Terrane were at 18.9°N, 208.4°E with A 95  = 3.9° and 19.6°N, 211.8°E with A 95  = 10.7°, respectively. We suggest that the Lhasa Terrane maintained a relative stable latitude (16.5 ± 3.9°S and 18.4 ± 10.7°S) in the southern hemisphere during the Triassic Period before moving northwards and amalgamating with the main body of Eurasia. The Qiangtang and Lhasa terranes, which were located at the mid-low latitudes of the southern hemisphere, might have been isolated between Eurasia and Gondwanaland since the Early Triassic Period. The Meso-Tethys, potentially represented by the Bangong–Nujiang suture zone (BNS) between the Lhasa and Qiangtang terranes, opened up in the Early-Middle Triassic Period and expanded during the entire course of the Triassic Period.